Limited spatial co-occurrence of wildfire and prescribed burning on moorlands in Scotland - Debbie Fielding; Scott Newey; Robin J. Pakeman; Dave Miller; Zisis Gagkas; Keith Matthews; Stuart W. Smith (Biological Conservation, 2024)

Increased grazing drives homogenisation but reduced grazing increases turnover in upland habitat mosaics - Robin J. Pakeman; Debbie A. Fielding (Biodiversity and Conservation, 2021)
Many ecosystems are grazed by livestock or large, wild herbivores and exist as mosaics of different vegetation communities. Changing grazing could have an impact on heterogeneity as well as on composition. A long-term, large-scale grazing experiment that maintained existing low-intensity sheep grazing, tripled it, removed it and partially substituted sheep grazing by cattle grazing was set up on a mosaic of upland vegetation types. The impact of changing grazing regimes was assessed in terms of changes in temporal and spatial species and functional beta diversity. Removal of grazing had the highest impact on species replacement, whilst increased grazing was closest to maintaining the original species complement. Wet heath and Molina mire had the lowest turnover, but wet heath showed the highest changes in unidirectional abundance as it contained species capable of increasing in abundance in response to changing grazing intensity. Agrostis-Festuca and Nardus grasslands displayed the highest level of balanced species replacement reflecting their more dynamic vegetation. In functional terms, there was no clear separation of communities based on their grazing preference, all were relatively resistant to change but Nardus grassland was the most resistant to the removal of grazing. The increased offtake associated with increased grazing led to a degree of homogenisation as grazing tolerant species associated with preferred communities increased in the unpreferred ones. Decisions about grazing management of the uplands involve many trade-offs, and this study identified potential trade-offs between stability and homogenisation to add to existing ones on the biodiversity of different groups of species and on ecosystem services.

Species composition of coastal dune vegetation in Scotland has proved resistant to climate change over a third of a century - Robin J. Pakeman; Jim Alexander; Joan Beaton; Rob Brooker; Roger Cummins; Antonia Eastwood; Debbie Fielding; Julia Fisher; Sarah Gore; Richard Hewison; Russell Hooper; Jack Lennon; et al. (Global Change Biology, 2015)
Climate change is expected to have an impact on plant communities as increased temperatures are expected to drive individual species' distributions polewards. The results of a revisitation study after c. 34 years of 89 coastal sites in Scotland, UK, were examined to assess the degree of shifts in species composition that could be accounted for by climate change. There was little evidence for either species retreat northwards or for plots to become more dominated by species with a more southern distribution. At a few sites where significant change occurred, the changes were accounted for by the invasion, or in one instance the removal, of woody species. Also, the vegetation types that showed the most sensitivity to change were all early successional types and changes were primarily the result of succession rather than climate‐driven changes. Dune vegetation appears resistant to climate change impacts on the vegetation, either as the vegetation is inherently resistant to change, management prevents increased dominance of more southerly species or because of dispersal limitation to geographically isolated sites.

Carcass Provisioning to Support Scavengers: Evaluating a Controversial Nature Conservation Practice - Debbie Fielding; Scott Newey; René van der Wal; R. Justin Irvine (Ambio, 2014)
A number of scavenger species have suffered population declines across Europe. In attempts to reverse their decline, some land and wildlife managers have adopted the practice of leaving or placing out carcasses of wild or domestic herbivores to provide a source of carrion. However, this can be a controversial practice, with as yet unclear outcomes for many target species and the ecosystems they are part of. Here we bring out the key aspects of this increasingly common conservation practice illustrated using three contrasting cases studies. We show that the provision of carcasses is often motivated by a desire to benefit charismatic species or to facilitate nutrient cycling throughout an ecosystem. Evidence for the effectiveness of this practice in achieving these objectives, however, is mostly lacking, with ecologists studying “easier” species groups such as beetles and therefore not providing relevant insights. Moreover, conflicts between environmental policies that carcass provisioning is aimed at and other social and economic objectives do occur but these projects are often designed without taking into account this broader context. We conclude that expecting carcasses to simply be “good for biodiversity” may be too naïve a view. A greater knowledge of the impact of carcass provisioning and placement on ecosystems and society at large is required before it can become a more effective conservation tool at a wider scale.